Application of a discrete adaptive LQG and fuzzy control design to a wind turbine benchmark model - Melício, Rui (2014)
This paper deals with a wind turbine control simulation supported by the use of computational tools appropriate to simulate complex systems. High performance and reliability are required for wind turbines to be competitive within the energy market. A key challenge for control systems is the wind power which is an uncontrolled input and also acts as a disturbance. A discrete adaptive LQG (linear quadratic) as well as a fuzzy PI control design of publicly available wind turbine benchmark models are proposed and simulation results by Matlab/Simulink are shown in order to prove the effectiveness of the design.